Comparison of Discharge Measurement Techniques for Small-scale Hydropower Efficiency - Cristian Purece (Current Approaches in Engineering Research and Technology Vol. 10, 2024)
Hydropower plants represent a large part of the portfolio of electricity production in Romania and provide about 25% of the electricity needs. Hydropower plants equipped with Kaplan turbines are generally low-head hydropower plants. This type of hydropower plants can process a discharge of the order of tens of m3/S (Vaduri HPP, Noaptesi HPP, Oesti HPP or hundreds of m3/s (Strejesti HPP, Câineni HPP) and generally have a low gross head of 15÷20m. On-situ determination of the efficiency of a turbine that equips a low-head hydropower plant, it is necessary to carry out some performance tests in situ by measuring the main operating parameters of the hydropower plant. Among the parameters of a hydropower plant, the parameter whose measurement poses the most difficult problems is the discharge, due to the short intaks and turbulences in the measuring section. The determination of this parameter requires a complex measurement methodology. This paper aims to present and analyze the main methods of in situ determination at low-head hydropower plants and awareness of the importance of carrying out on-site tests to determine the discharge and real operating characteristics. Based on the actual operating characteristics, the optimal operating area can be determined, and the operation of the turbine within this optimal operating area will lead to an increase in the energy production obtained by the turbine of the same volume of water.